HUBUNGAN EMOTIONAL COPING BEHAVIOR DENGAN AGRESIVITAS SUPORTER SEPAK BOLA BONEK MANIA - Syaiba, Abdulloh Alba (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2021)
The study would like to see the relationship of emotional coping behavior with the aggressiveness of bonek mania soccer supporters. This research is a correlational quantitative study. The sample used in this study is 197 bonek mania supporters selected through a simple random sampling technique. The research instrument was a way of coping scale for the emotional-focused coping scale and an aggression questionnaire scale for the aggressiveness scale. Pearson's Product Moment Analysis on SPSS version 2.2 for Windows shows a correlational value of 0.271 with a significance value of 0.000 (<0.05). The results indicate that there is a correlation between emotional coping behavior and aggressive Bonek Mania.